Occupational noise exposure among construction workers - Dawi, Stephanie Stella (2013)
Construction activities often generate noise complaints despite a short period of time framed over it takes place. One of the major contributions in noise is the construction equipments which tend to produce a high noise level. However, the noises from construction equipments do expose the workers who handle the task. Studies have shown most of the noise exposure do harm the safety and health of workers. This study focuses on (1) obtaining noise level among construction workers, (2) the compliance of permissible noise exposure level among workers; (3) assess the awareness and perceptions of noise exposure among workers and (4) explore the perceptions of noise impacts to safety and health workers. Occupational noise exposures for one hour among construction workers were assessed using noise dosimeters for on-site measurement and questionnaire surveys at the study construction site. The results for projection eight hours showed that almost all the activities exceeded the recommended noise level permitted by HSE whereas only one of the activities exceeded the FMR first schedule and OSHA permissible limit. For questionnaire surveys, the level awareness was encouraging yet a slight percentage revealed about the effects of noise in terms of age and work experience of respondents. Consequently, more approaches on the importance of noise exposure should be taken into consideration in order to improve awareness and mitigates the noise exposure.